PENDAMPINGAN PENGAJUAN SERTIFIKASI HALAL SELF DECLARE BAGI PELAKU USAHA DI KECAMATAN TELUK PANDAN KABUPATEN KUTAI TIMUR - Mustatho, Mustatho; Muchammad Abdul Basir (P3M STAI Sangatta, 2025)
This community service is carried out in the form of mentoring for micro, small and medium enterprises (MSMEs) in Teluk Pandan District in applying for halal certification through self-declaration in the One Million Free Certificates (SEHATI) program. The majority of micro, small and medium enterprises (MSMEs) in Teluk Pandan District, East Kutai Regency do not yet understand the procedures for applying for halal certification, the requirements and the classification of products that may be registered. Therefore, this mentoring service focuses on: 1) providing an understanding of the importance of halal certification, 2) providing training on procedures for applying for halal certification for the SEHATI program, and 3) providing assistance for halal certification registration through the Sihalal application. The method of implementing community service activities carried out by this service team uses the Participatory Action Research approach, namely assisting and providing a role so that business actors directly practice and carry out all halal certification application processes through the Sihalal application. The results of this community service activity are that business actors get a business registration number as one of the requirements for applying for halal certification through SEHATI and the issuance of halal certificates for the products they apply for. With the halal certificate, consumers will no longer hesitate to buy and consume products from business actors in Teluk Pandan District, East Kutai Regency.